CONSTITUENCIES OF JOURNALS IN PRODUCTION AND OPERATIONS MANAGEMENT: IMPLICATIONS ON REACH AND QUALITY* - AGRAWAL, VIJAY K. (Production and Operations Management, 2002)
I analyzed the contributions made by members of the following constituencies in terms of the number of articles published in the Journal of Operations Management (JOM), Manufacturing and Service Operations Management (M&SOM), and Production and Operations Management (POM): the top 20 U.S. business schools and the top 7 non‐U.S. business schools as ranked by Business Week or U.S. News and World Report, business and government organizations, U.S. business schools ranked between 21 and 50, non‐U.S. business schools not included above, and U.S. business schools not included above. I also analyzed the contributions made by U.S. business schools with top 10 programs in production and operations management; 9 of which are also in the list of top 20 U.S. business schools. Authors from the schools with top 10 programs in production and operations management contributed 20.2% of the articles published in POM and 3.5% of the articles published in JOM during 1997‐2001. They contributed 24.6% of the articles in the eight issues (from July 2000 through June 2002) of M&SOM. During these periods, authors from the top 27 schools contributed 29.3% of the articles published in POM, 9.4% of the articles published in JOM, and 37.4% of the articles to the eight issues of M&SOM. Also during the same periods, authors from business and government organizations contributed 6.6% of the articles published in POM, 1.9% of the articles published in JOM, and 5.8% of the articles published in the eight issues of M&SOM. The findings reported in this paper reflect the reach of the three journals and the perceptions of various constituencies regarding journal quality. The findings about POM and JOM have a very high degree of validity because both journals are more than 10 years old and have well‐established constituencies. The conclusions about the M&SOM constituencies are tentative because it is about 3 years old, and it is still developing its constituencies.